Integrated Quality Management Model of Learning Practices in Tourism Vocational Higher Education - Deden Saepudin; Udin Syaefudin Sa'ud; Diding Nurdin; Taufani Chusnul Kurniatun (STAI Hubbulwathan Duri, 2023)
This study aims to analyze tourism education activities, especially regarding the management of practical learning at vocational tertiary institutions in the field of tourism. The research method uses a qualitative approach with a case study type approach, mixed methods sequential exploratory design. Resource persons or research informants consist of. Directors, Heads of Study Programs, Lecturers, Practical Instructors, Heads of Internal Quality Assurance, and students at the two institutions that are the locus of research. The results of the study show that practical learning activities at vocational tourism colleges have not been managed optimally. Furthermore, this study offers a competency-based practical learning quality management hypothetical model that is integrated with industry as an alternative solution in managing practical learning activities to improve the quality of learning outcomes and produce graduates who have skills and competencies that meet industry standards and needs. This model carries university collaboration. tourism with the hospitality industry in organizing practical learning activities. This form of collaboration is realized by involving industrial practitioners in a number of learning activities, including 1) Curriculum development and alignment; 2) Formation of a Steering Committee; 3) Teaching practitioner program; 4) Implementation of fieldwork practice programs; 5) Sending students to work part-time (daily workers); and 6) Guest lectures from industry practitioners. Recommendations and implications of this research are the need to build good collaboration between universities and industry in managing practical learning activities that link and match.